Contribution of groundwater carbon pools to atmospheric carbon sinks: A case study of the Yinchuan Basin, Northwest China - Hong-yun Ma; Jiang Liu; Hong-na Ma; Hua-qi Wang; Cheng-zhu Li; Yan-e Li (China Geology)
ABSTRACT: Addressing global warming, a common change today, requires achieving peak carbon dioxide emissions and carbon neutrality (also referred to as the dual carbon goals). Enhancing research on the carbon cycle is urgently needed as the foundation. Water, a key carrier in the carbon cycle, necessitates investigation into groundwater carbon pools’ contribution to atmospheric carbon sinks. This study assessed carbon stocks in the Yinchuan Basin's soil and groundwater carbon pools. Findings indicate the basin's surface soils contain approximately 24.16 Tg of organic carbon and a total of 60.01 Tg of carbon. In contrast, the basin’ s groundwater holds around 4.90 Tg of carbon, roughly one-fifth of the organic carbon in surface soils. Thus, groundwater and soil carbon pools possess comparable carbon stocks, underscoring the importance of the groundwater carbon pool. Studies on terrestrial carbon balance should incorporate groundwater carbon pools, which deserve increased focus. Evaluating groundwater carbon pools’ contributions is vital for achieving the dual carbon goals.